Synthesis and Structural Characterization of Supramolecular Mn(II)-Li(I) Complex with Salen-Type Bisoxime - Dong, Xiu-Yan; Wang, Li; Yang, Yu-Hua; Wang, Fa; Li, Yuan (Asian Journal of Chemistry, 2013)
Supramolecular manganese(II)-Li(I) complex, [MnL(OH)(H2O)Li]n, has been prepared and characterized by elemental analyses, FT-IR, UV-visible spectra, molar conductance measurement and X-ray crystallography (where H2L = 4,4',6,6'-tetrachloro-2,2'-[ethylenedioxybis(nitrilomethylidyne)]diphenol). The complex is self-assembled using various non-covalent interactions including hydrogen bonding interactions and p-p stacking to form chain supramolecular structure.